The relationship between isometric mid-thigh pull variables, jump variables and sprint performance in collegiate soccer players - Kuki, S.; Sato, K.; Stone, M. H.; Okano, K.; Yoshida, T.; Tanigawa, S. (Journal of Trainology, 2017)
Objectives: The purpose of this study was to examine the relationship among isometric mid-thigh pull (IMTP) variables, jump variables and sprint times in collegiate soccer players. Additionally, this study was conducted to demonstrate that strength characteristics influence the relationship between jump variables and sprint times. Design and Methods: Twenty-five collegiate soccer players performed IMTP, jump and sprint assessments. For IMTP, the force output at 100ms (F100ms) and peak force (PF) were analyzed. Countermovement jump (CMJ) and drop jump (DJ) index were measured. A 30m sprint was performed, and the times at 10m, 20m and 30m were recorded. Pearson`s product-moment correlation and a one-way analysis of variance (ANOVA) were used at p = 0.05. A cluster analysis was performed to divide all the subjects. Results: The F100ms significantly correlated with DJ-index (r = 0.433) and sprint times at 20-30m (r = -0.444). All the subjects were separated into high (HG: N = 9), medium (MG: N = 7) and low (LG: N = 9) groups based on the F100ms, because the coefficient of variation for F100ms was high (34.3%). There was a strong significant relationship between CMJ and sprint time at 10-20m in HG (r = -0.915), however there were no significant relationship in MG and LG. Conclusions: The F100ms can be used as an indicator for identifying athletes who have a statistically significant relationship between CMJ and flying sprint times. The results of the present study suggested that coaches should realize F100ms might pro vide the foundation to improve the sprint performance.